2014
DOI: 10.3846/13923730.2013.802729
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Influence of Stack Effect on Fire in the Compartment Adjacent to Stairwell of High Rise Building

Abstract: In this paper, to study the influence of stack effect on fire in the compartment adjacent to a stairwell, a set of experiments were conducted by varying the pool size, top vent state and bottom vent size in a 1/3 scaled 12-layer-stairwell configuration. The phenomenon of methanol flame tilting in the fire room was observed and studied. Results showed that the flame tilt angle increases with an increase of Ri -1 . The temperatures of hot gases in the fire room decrease due to the cooling effect of fresh air ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…The stack effect is normally formed when the indoor temperature is higher than the outdoor temperature and the fresh air flows into the stairwell from the lower opening and smoke flows out from the upper opening. On the contrary, the reverse stack effect forces the air to flow at an opposite direction [2,7,8]. As reported by Qi et al [9], fire-induced smoke may arrive at higher levels easily via the vertical shafts driven by stack effect.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The stack effect is normally formed when the indoor temperature is higher than the outdoor temperature and the fresh air flows into the stairwell from the lower opening and smoke flows out from the upper opening. On the contrary, the reverse stack effect forces the air to flow at an opposite direction [2,7,8]. As reported by Qi et al [9], fire-induced smoke may arrive at higher levels easily via the vertical shafts driven by stack effect.…”
Section: Introductionmentioning
confidence: 83%
“…From the follow analysis, the direction and dominant mechanism of gas flow can be obtained. In the first series cases, the large airflow velocity at the lower opening with no temperature rise indicates that fresh air flows into the lower opening while no smoke flows out of this opening, similar as [3] and [8]. The airflow velocity at the upper opening with temperature rise indicates smoke flowing out.…”
Section: Flow Velocity and Temperature At The Openingsmentioning
confidence: 89%
“…Using the image processing method, the flame height and area at different time were obtained from the camera video. The image processing method, which has been employed in previous works, is introduced as follows. With the video process software (Premiere), the flame‐spread video was transformed into frames of images.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…According to Figure 8, it could be found that V air had a significant effect on smoke spread in the cavity. The value of V air increased markedly with a decrease in fire room height owing to the influence of stack effect (Yang et al 2013;Shi et al 2014). When the fire source was located on the 2 nd floor, the moving path of smoke in the cavity was longer, and stack effect was stronger.…”
Section: Effects Of Fire Room Heightmentioning
confidence: 95%